Design, synthesis and applications of hydroxylmethyl-aryl phosphine oxides in phosphorus catalysis - Chapman, Charlotte Grace (2015)
Organophosphorus-mediated reactions are important tools in organic chemistry and are used in the synthesis of highly desirable drug targets, such as morphine.1 A major drawback of traditional phosphorus-mediated reactions is the formation of stoichiometric amounts of phosphine oxide by-products; this renders the product purification difficult and reduces the atom efficiency of these transformations. For these reasons, catalytic variants become desirable; there being two potential strategies to achieve the catalysis; i) redox-driven and ii) redox-neutral.2-4 The redox-driven catalytic cycle requires a reductant for the turnover whilst the redox-neutral system uses a sacrificial reagent to directly turn over the phosphine oxide to the active phosphorus (V) reagent. This thesis will report upon a new class of Hydroxylmethyl-Aryl phosphine 1 and phosphine oxide 3 catalyst for use in a redox-driven catalytic reaction; the Staudinger reduction Scheme 1, and routes to a potential redox-neutral catalytic Mitsunobu reaction Scheme 2.